Multiomic neuropathology improves diagnostic accuracy in pediatric neuro-oncology - Sturm, Dominik; Capper, David; Andreiuolo, Felipe; Gessi, Marco; Kölsche, Christian; Reinhardt, Annekathrin; Sievers, Philipp; Wefers, Annika K.; Ebrahimi, Azadeh; Suwala, Abigail Kora; Gielen, Gerrit H.; Sill, Martin; et al. (Nature medicine, 2023)
The large diversity of central nervous system (CNS) tumor types in children and adolescents results in disparate patient outcomes and renders accurate diagnosis challenging. In this study, we prospectively integrated DNA methylation profiling and targeted gene panel sequencing with blinded neuropathological reference diagnostics for a population-based cohort of more than 1,200 newly diagnosed pediatric patients with CNS tumors, to assess their utility in routine neuropathology. We show that the multi-omic integration increased diagnostic accuracy in a substantial proportion of patients through annotation to a refining DNA methylation class (50%), detection of diagnostic or therapeutically relevant genetic alterations (47%) or identification of cancer predisposition syndromes (10%). Discrepant results by neuropathological WHO-based and DNA methylation-based classification (30%) were enriched in histological high-grade gliomas, implicating relevance for current clinical patient management in 5% of all patients. Follow-up (median 2.5 years) suggests improved survival for patients with histological high-grade gliomas displaying lower-grade molecular profiles. These results provide preliminary evidence of the utility of integrating multi-omics in neuropathology for pediatric neuro-oncology.